Fluconazole in the Treatment of Cutaneous Leishmaniasis Caused by Leishmania braziliensis: A Randomized Controlled Trial - Prates, Fernanda V de O; Dourado, Mayra E F; Silva, Silvana C; Schriefer, Albert; Guimarães, Luiz H; Brito, Maria das Graças O; Almeida, Juliana; Carvalho, Edgar M; Machado, Paulo R L (Clinical infectious diseases, 2017)
The treatment of cutaneous leishmaniasis (CL) caused by Leishmania braziliensis in Brazil with pentavalent antimony (Sb ) is associated with a high rate of failure, up to 45% of cases. In addition, Sb can only administered parenterally and has important toxic effect. An effective, safe, and oral treatment for CL is required. A randomized controlled clinical trial was conducted to compare the efficacy and safety of high-dosage oral fluconazole (6.5-8.0 mg/kg/d for 28 days) versus a standard Sb protocol (20 mg/kg/d for 20 days) for the treatment of CL in Bahia, Brazil. A total of 53 subjects were included in the trial; 26 were treated with Sb , and 27 with fluconazole. Intention-to-treat analysis showed initial cure rates (2 months after treatment) of 22.2% (6 of 27) in the fluconazole and 53.8% (14 of 26) in the Sb group (P = .04). Six months after treatment, the final cure rate remained the same in both groups, without any relapses. The frequencies of adverse effects in the Sb and fluconazole groups were similar, 34.6% versus 37% respectively. One patient treated with fluconazole discontinued treatment owing to malaise, headache, and moderate dizziness (Common Terminology Criteria for Adverse Events grade 2). Oral fluconazole at a dosage of 6.5-8 mg/kg/d for 28 days should not be considered an effective treatment for CL caused by L. braziliensisClinical Trials Registration. NCT01953744.